Application of the Jerusalem artichoke (Helianthus tuberosus L.), as a plant origin medium additive, during the micropropogation of Ada keiliana - Eszéki, R. E.; Tilly-Mándy, A. (International Journal of Horticultural Science, 2008)
A procedure for in vitro propagation of Ada keiliana seedlings are suited for acclimatization, was worked out. M medium was supplemented, with Jerusalem artichoke, as plant origin complex additive. The apply of JAD (1,5g/flask) gave the best response, considering the shoot (29 mm), and the root development (24,9) mm) too. The plantlets with satisfying growth (25-30 mm, 4-5 roots) were transferred in small pine bark: Novobalt peat: coconut fibres: perlit (2:3:1:1) mix, among greenhouse circumstances.